Human resource management practices: and a study on talent acquisition & selection process of Digicon Technologies ltd. - Hossain, Md. Nur (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.